Safety Profile of Biological Drugs in Clinical Practice: A Retrospective Pharmacovigilance Study - Hassan, Elaaf Fadhil; Kadhim, Dheyaa j; Younus, Manal m (Iraqi Journal of Pharmaceutical Sciences, 2022)
Biological drugs have an active substance that is made by a living organism or derived from a living organism. They are one of the important therapy options used in a wide range of diseases especially life-threatening diseases. Biological therapy opens new opportunities for treating different diseases for which drug therapy is minimal, but they have considerable differences in the safety consequences in comparison with non-biological drugs. The aim of the current study was to assess the post-marketing safety proﬁle of biological drugs used in Iraqi hospitals by the analysis of the reported adverse drug reactions regarding their severity, seriousness, preventability, expectedness, and outcome. It is a retrospective study of the individual case safety reports from the Iraqi Pharmacovigilance Center/Ministry of Health. There were 446 individual case safety reports in the research, involving 899 adverse drug reactions. Rituximab was found to be the drug with the highest number of adverse drug reactions with 241 adverse drug reactions (26.81% out of total adverse drug reactions). Most of the adverse drug reactions were related to general disorders and administration site conditions (22.25%). Regarding severity of adverse drug reactions, the majority of adverse drug reactions were observed in moderate levels [Level 4 (26%), and Level 3 (18%)]. The severe adverse drug reactions in patients below 18 years age group were significantly higher compared to adults and elderly. Seriousness assessment showed that the majority of adverse drug reactions were serious (52%). Rituximab was the drug for which the highest number of serious adverse drug reactions was reported (41.28% of total serious adverse drug reactions), Most of the adverse drug reactions (66%) were probably preventable. Fatality outcome was reported for 3% of adverse drug reactions while 43% of adverse drug reactions were recovered/resolved.